THE INFLUENCE OF PRACTICE FACILITIES DAN PRACTICE LEARNINGIN MOTIVATION TOWARD THE IMPORVEMENT OF LEARNING ACHIEVEMTN OF HYDROLIC SYSTEM AMONG THE ELEVENTH GRADE STUDENTS OF SMK TAKAHUS WONOSOBO IN THE ACADEMIC YEAR 2013/2014 - Adi Nika Prasetyo; Subagyo Subagyo (Universitas Sarjanawiyata Tamansiswa, 2014)
The objectives of this tudy are to describe (1) the influence of learning facilities toward the learning achievement of hydrolic system, (2) the influence of practice learning motivation toward the learning achievement of hydrolic system, and (3) the influence of learning facilities and practice learning motivation toward the learning achievement of hydrolic system in the academic year 2013/2014. This study shows that (1) there is a positif and significant learning facilities toward the learning achievement of hydrolic system, (2) there is a positif and significant practice learning motivation toward the learning achievement of hydrolic system, and (3) there is a positif and significant learning facilities and practice learning motivation toward the learning achievement of hydrolic system in the academic year 2013/2014. The practice learning motivation and learning facilities can improve knowledge, desire of the students to develop their knowledge and creativity in learning, so that the result of learning can be improved. The better practice learning motivation and learning facilities, soothe better improvement of learnig achievement of hydrolic system.